Modular gene analysis reveals distinct molecular signatures for subsets of patients with cutaneous lupus erythematosus. (3rd March 2021) - Zhu, J. L.; Tran, L. T.; Smith, M.; Zheng, F.; Cai, L.; James, J. A.; Guthridge, J. M.; Chong, B. F.
Summary: Background: Cutaneous lupus erythematosus (CLE) is a heterogeneous autoimmune disease with clinical sequelae such as itching, dyspigmentation and scarring. Objectives: We applied a previously described modular analysis approach to assess the molecular heterogeneity of patients with CLE. Methods: Whole‐blood transcriptomes of RNA sequencing data from a racially and ethnically diverse group of patients with CLE ( n  = 62) were used to calculate gene co‐expression module scores. An unsupervised cluster analysis and k ‐means clustering based on these module scores were then performed. We used Fisher's exact tests and Kruskal–Wallis tests to compare characteristics between patient clusters. Results: Six unique clusters of patients with CLE were identified from the cluster analysis. We observed that seven inflammation modules were elevated in two clusters of patients with CLE. Additionally, these clusters were characterized by interferon, neutrophil and cell‐death signatures, suggesting that interferon‐related proteins, neutrophils and cell‐death processes could be driving the inflammatory response in these subgroups. Three different clusters had a predominant T‐cell signature, which were supported by lymphocyte counts. Conclusions: Our data support a diverse molecular profile in CLE that further adds to the clinical variations of this skin disease, and may affect disease course and treatment selection. Future studies with a larger and diverse cohort of patients with CLE are warranted to confirm these findings. Abstract : What is already known about this topic? Cutaneous lupus erythematosus (CLE) is a clinically heterogenous disease. Patients of different CLE subtypes largely receive the same first‐line treatments. What does this study add? Modular gene expression analysis identified six CLE subsets distinguished by modules related to cell types and cell processes. Two groups of patients with CLE had inflammation and neutrophil signatures. Three clusters of patients with CLE had elevated T‐cell module scores. What is the translational message? The molecular diversity of patients with CLE may reveal a greater heterogeneity in CLE than previously recognized by clinical phenotypes. These have implications for targeted therapies for different subsets of patients with CLE. Linked Comment:  T. Vazquez et al. Br J Dermatol 2021; 185:480–481 . Plain language summary available online